Development of a Structural Model for Constructing a Cutting Tool Trajectory Analysis Module in the Axiom Control CNC System (London Journal of Engineering Research, 2025)
Justification. Currently, metalworking machines are used in various industries. The operation of these machines, designed for numerical control (CNC), is impossible without the use of appropriate systems that allow for the operational configuration of the system to solve various technological problems by controlling the machine’s drives. The purpose of this work is to comprehensively analyze the functionality of the Axiom Control CNC visualization module in order to identify its strengths and weaknesses compared to similar systems on the market. In the course of the research, a detailed review of existing technologies and visualization methods used in numerical control systems will be conducted, which will allow for a deeper understanding of current trends and needs in this area. Materials and methods. To achieve this goal, the following task has been set, aimed at expanding the functionality of the cutting tool rendering module in the Axiom Control CNC system, namely, the analysis of existing visualization tools for the trajectory of cutting tools in CNC systems.
Keywords: Carbon nanotubes (CNTs); Functionalization of CNTs; Chirality; Arc discharge; laser ablation; Biosensors.; manufacturing.; industry; Technological tasks; metalworking; visualization of the axiom control CNC system